Modelagem matemática, serviços ecossistêmicos e análise da paisagem como ferramentas no manejo de reservatórios inseridos em áreas antropizadas - Silva, Fabio Leandro da (Universidade Federal de São Carlos, 2022)
In the last decade, a water crisis has been experienced that has negatively impacted several economic sectors and caused adverse effects that interfere with the maintenance of aquatic systems. Reservoirs are artificial systems that play an important role in the electricity generation and water storage, but many socio-environmental impacts are observed during their construction and those systems have been impacted by anthropogenic activities. Therefore, there is a need to use approaches that enable the evaluation of these systems, as well as the establishment of management strategies. For that, we used: (i) a zero-dimensional model to verify the mass balance of limnological variables; (ii) quality management tools for analyzing limnological data; (iii) landscape analysis and use of a landscape structure indicator; and (iv) a qualitative approach to the assessment of ecosystem services. Upstream and downstream points of the Barra Bonita (RBB), Salto Grande (RSG), Itupararanga (RI) and Jaguari-Jacareí (RJJ) reservoirs were evaluated, considering the rainy (January, March, November) and dry seasons (May, July, September). Data from the ‘Companhia Ambiental do Estado de São Paulo’ (CETESB) were used for the following variables: electrical conductivity (EC), thermotolerant coliforms (FC), biological oxygen demand (BOD5,20), dissolved oxygen (DO), total chloride (CHL), ammonia nitrogen (NH4), nitrate (NO3), nitrite (NO2), pH, turbidity (TURB), total phosphorus (TP), and total solids (ST). In RBB, upstream stations of the Tietê and Piracicaba rivers were evaluated, as well as a downstream station in the Tietê river. Considering the RSG, an upstream and downstream station on the Atibaia river was evaluated. In the case of the RI, three upstream stations (Una, Sorocabuçu and Sorocamirim rivers) and other downstream, close to the dam, were evaluated. Concerning RJJ, two stations were verified in the Jaguari river: one upstream and the other downstream. In terms of mathematical modeling, RBB demonstrated a good capacity to retain limnological variables, especially those related to the sedimentation process. Considering the guiding values of CONAMA Resolution 357/05 and CETESB, it was found that BBR, SGR and RI had the highest number of non-conformities. EC, FC, BOD5,20, DO and TP are responsible for most non-conformities. In relation to the land cover of the Piracicaba-Capivari-Jundiaí and Sorocaba-Médio Tietê Water Resources Management Units between 2010 and 2020, the predominance of anthropogenic uses (agricultural and urbanized areas) is evident, which occupy more 60% of the territory, despite the native vegetation recovery. The Distance to Nature (D2N) showed the predominance of urbanized/intensively cultivated landscapes (> 60%), as well as areas that were unchanged and changed in natural or artificial direction. As for ecosystem services, it was shown that changes in limnological variables affect the maintenance of biodiversity and directly impact the provision of ecosystem services. It is recommended the implementation of strategies that contribute to the improvement of the environmental quality of the study area and water bodies, the approach was useful for the evaluation of these ecosystems and contributes to the decision making.
Mathematical modeling, ecosystem services and landscape analysis as tools in the management of reservoirs inserted in anthropized areas
Keywords: Ecossistemas artificiais; Balanço de massa; Ferramentas de gestão da qualidade; Usos da terra; Indicador ambiental; Bacias hidrográficas; Artificial ecosystems; Mass balance; Quality management tools; Land uses; Environmental indicator; Watersheds; CIENCIAS BIOLOGICAS::ECOLOGIA